Consumer Behavior Analysis in Buying Used Cars through Electronic-Based Auction Applications OLX Autos Semarang City - Adityamurti, Enggar; Kusumawardhani, Amie (Politeknik Siber Cerdika Internasional, 2024)
This research examines OLX Autos users, namely one of the electronic service providers available for fast processing and fulfillment of each transaction related to electronic automotive auctions in Indonesia. This study aims to determine the effect of attitudes and subjective norms on purchase intentions and their influence on purchasing decisions at OLX Autos electronic auctions. The sample used in this study was 175 respondents or users of the OLX Autos application. The data analysis method used in this study is Partial Least Square using Smartpls software. The test results show that attitudes have a positive and significant effect on purchase intention. Subjective Norms have a positive and significant effect on purchase intention. Attitude has a positive and significant effect on purchasing decisions. Subjective norms have a positive and significant effect on purchasing decisions. And buying interest has a positive and significant effect on purchasing decisions.